Granulocyte-colony-stimulating factor mobilizes bone marrow stem cells in patients with subacute ischemic stroke: the Stem Cell Trial of Recovery EnhanceMent After Stroke (STEMS) Pilot Randomized, Controlled Trial (ISRCTN 16784092) - Sprigg, Nikola; Bath, Philip M.W.; Zhao, Lian; Willmot, Mark; Gray, Laura J.; Walker, Marion F.; Dennis, Martin S.; Russell, Nigel (American Heart Association, 2006)
Background and Purpose - Loss of motor function is common after stroke and leads to significant chronic disability. Stem cells are capable of self-renewal and of differentiating into multiple cell types, including neurones, glia, and vascular cells. We assessed the safety of granulocyte-colony-stimulating factor (G-CSF) after stroke and its effect on circulating CD34 stem cells.